The Speed of Rational Learning - Alvaro Sandroni (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
A stage game is played infinitely many times. After observing the outcomes of the games, players revise their beliefs about opponents' strategies. I show the general conditions under which players' predictions become accurate fast. Key words: Repeated Games, Rational Learning, Speed of Convergence Journal of Economic Literature classification number: D83 Learning.
Keywords: 330